PARTISIPASI MASYARAKAT DALAM PENGELOLAAN HUTAN MANGROVE DI DESA BUANO SELATAN KABUPATEN SERAM BAGIAN BARAT - Kerlirey, Muhammad; Tjoa, Marthina; Iskar, Iskar (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This study aims to determine the form of mangrove forest management and the level of community participation and community supervisory groups in mangrove management in South Buano village. The research was conducted in February - March 2023. Samples were taken using the purposive sampling method and data analysis was carried out descriptively qualitatively and quantitatively. The research results show that the form of mangrove management by the community is carried out based on community knowledge to protect and maintain mangroves. There is a Community Monitoring Group (Pokmaswas) organization that was formed for mangrove management with activities including planning, seeding, maintenance, monitoring and trash cleaning activities in mangrove areas. The level of community participation in mangrove forest management in South Buano village has the highest incentive participation category in seeding, planting and maintenance activities.